Effects of scaling on high subsonic cavity flow oscillations and control - Thangamani, Varun; Knowles, Kevin; Saddington, Alistair J. (AIAA, 2014)
The effects of scaling on cavity oscillations and control have been studied by measuring the unsteady pressure on the floor of three cavities of different scales. The cavities have a length-to-depth ratio of 5 and a length-to-width ratio of 2, and the corresponding linear dimensions are in the ratio0.5∶1∶2. The experiments were conducted with clean cavities and cavities fitted with leading-edge sawtooth spoilers so as to study the influence of scaling on clean cavities as well as the effectiveness of the passive control method on different sized cavities. The results showed significant variation of certain spectral characteristics of the clean cavities. The control effectiveness of the spoilers also showed variations with a change in scale of the model. It is recommended that, before implementing a passive control device for practical applications, the device should be tested in the possible range of cavity length-to-boundary-layer-thickness ratio (L/δ) that can be experienced in actual flight.